Aplicação da logística de armazenagem e distribuição em uma Indústria de refrigerantes: um estudo de caso - Azevedo, Hordônio Chagas (2018)
This work aims to investigate the factors that guide integrated logistics in a soft drink industry, more specifically in the process of storage, transportation and physical distribution, processes that generate a competitive differential for companies in the world. Increasingly present in companies, the integration of the supply and supply chain has expanded, taking increasing proportions leading companies to increasingly manage the value chain through the connection between customers and suppliers in order to better distribute the added value products and services. The study of the concept of supply chain management and its application through logistics activities, especially in the stages of storage, transportation and distribution to put the right product, at the right time, in the right place and in the quantity needed, is the main objective this work. In order to identify an operational application of logistic concepts in the supply chain, a case study was conducted in a beverage industry, the franchisee of a multinational of soft drinks that has in its area of activity the states of Ceará, Bahia, Rio Grande do Norte, Piauí, Maranhão, Mato Grosso, Sergipe, Alagoas, Paraíba and Pernambuco. Rationale for bibliographical review on basic concepts and logistics evaluation, study of their opinion on the industries, analysis of their supply chain, highlighting as main points and distribution in areas of own and outsourced service, to highlight their competitive advantages and their points of improvement within the context of their supply chain, there is no need to add more value to their customers.